"Nom quer'eu donzela fea" : misoginia nas cantigas satíricas de Afonso X - Tavares, Vanessa Giuliani Barbosa (2018)
The goal of this research is to study the feminine characters in the satirical songs of Alfonso X, King of Castile and Leon and troubadour, based on philological, literarycritical, historiographical and philosophical interdisciplinary studies. It approaches the clerical, legal and philosophical discourses from Antiquity and Middle Ages that consolidated the western misogynist tradition and engendered the social condition of women between the 12th and 14th centuries, identifying the aesthetic and behavioral models prescribed for medieval nobles and commoners. Based on investigation of social criteria regarding beauty and ugliness, this analysis recognizes the feminine ugliness as one of the motivators of laughter in the Galician-Portuguese escárnio e maldizer, observing some poetical-rhetorical strategies applied by the troubadours to describe ladies, old women and soldadeiras and their physical and moral characteristics condemned by medieval paradigms. In view of this, it is verified that the satirical songs of Alfonso X, although focused on entertainment, are as equally configured as a literature which, by pointing out the misfit of satirized women to the prescribed models of beauty and conduct, became a means of diffusion and maintenance of medieval misogyny, that is, the essentialist discourses that promoted the social and historical vanishing of the feminine gender.